2017
DOI: 10.1080/15548627.2016.1268302
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation targets HSD17B4 for degradation via the CMA pathway in response to estrone

Abstract: Dysregulation of hormone metabolism is implicated in human breast cancer. 17b-hydroxysteroid dehydrogenase type 4 (HSD17B4) catalyzes the conversion of estradiol (E2) to estrone (E1), and is associated with the pathogenesis and development of various cancers. Here we show that E1 upregulates HSD17B4 acetylation at lysine 669 (K669) and thereby promotes HSD17B4 degradation via chaperonemediated autophagy (CMA), while a single mutation at K669 reverses the degradation and confers migratory and invasive propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The degradation of HSD17B4 triggered by DHT also suggests a negative feedback mechanism. A previous study showed that K669 acetylation promotes HSD17B4 degradation through CMA [ 22 ]. We then examined the K669 acetylation level and found that 10 nM DHT increased the K669 acetylation level in both a time-dependent and dose-dependent manner ( Figure 4A – 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of HSD17B4 triggered by DHT also suggests a negative feedback mechanism. A previous study showed that K669 acetylation promotes HSD17B4 degradation through CMA [ 22 ]. We then examined the K669 acetylation level and found that 10 nM DHT increased the K669 acetylation level in both a time-dependent and dose-dependent manner ( Figure 4A – 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that SIRT3 is responsible for acetylation of HSD17B4 in breast cancer cells [ 22 ]. We transfected HA-tagged SIRT3 and FLAG-tagged HSD17B4 into LNCaP cells and determined the acetylation level of HSD17B4 by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…The association between dysregulation of hormone metabolism and human breast cancer and sirtuin expression was described by Zhang et al [ 47 ]. 17β-hydroxysteroid dehydrogenase type 4 (HSD17B4) catalyzes the conversion of estradiol (E2) to estrone (E1), and is associated with the pathogenesis and development of various cancers, especially those which are hormone-dependent.…”
Section: Sirtuins In Typical Women’s Cancersmentioning
confidence: 99%
“…There is a correlation between CMA activity and metastasis in breast cancer [ 75 ]. CMA degrades the multifunctional protein HSD17B4, which modulates the properties for the invasion and migration of cells [ 103 ]. Moreover, decreased CMA by the modulation of LAMP2A inhibits tumor growth and metastasis by upregulating ATG5-dependent macrophages in human breast cancer [ 75 ].…”
Section: The Bipolar Role Of Autophagy In Cancermentioning
confidence: 99%